Length of stay and determinants of early discharge and extended stay after cesarean delivery in a resource-limited setting: southern Ethiopia, 2023 - Kitil, Gemeda Wakgari; Birgoda, Gebremaryam Temesgen; Walle, Agmasie Damtew; Dinagde, Dagne Deresa; Feyisa, Gizu Tola; Gebrehiwot, Yosef Alemayehu; Degefa, Bekem Dibaba (Frontiers in Global Women's Health, 2024)
BackgroundFor mothers and newborns to obtain the recommended postnatal care follow-up and package, the healthcare facility has to provide a minimum length of stay following delivery. Early discharge may result in a shortened recovery time, less access to resources and support, and a prolonged stay, resulting in a greater risk of postpartum depression and financial constraints. In Ethiopia, there has been no study conducted on the length of hospital stays following a cesarean delivery. Therefore, this study aimed to determine the average length of stay and identify factors influencing both early discharges and prolonged stays after cesarean delivery in southern Ethiopia.MethodsA facility-based cross-sectional study was conducted between November 23, 2022, and March 23, 2023. A systematic sampling method was used to select 367 participants, and data were collected using the Kobo Toolbox mobile application. The mean length of stay was calculated in hours, and descriptive statistics were used to summarize the data. Multinomial logistic regression was employed to analyze the determinants of length of stay, with significance set at a p-value of <0.05.ResultsThe mean duration of the length of stay of mothers in health facilities after cesarean delivery is 65 h or approximately 2.71 days (SD ± 0.77). Determinants of shorter stay included women aged 20–24 years [AOR = 5.19; 95%CI 1.51–8.23], distance from hospital 30–60 min [AOR = 2.51; 95% CI 1.12–5.73], first antenatal booking [AOR = 0.16; 95%CI 0.05–0.25], monthly income <2,000 birr [AOR = 3.11; 95%CI 1.18–6.05], had health insurance [AOR = 0.35; 95% CI 0.26–0.37] and had counseled [AOR = 0.09; 95%CI 0.07–0.154]. Extended stays were associated with severe pre-eclampsia [AOR = 2.80; 95%CI 2.41–3.27], multiple births [AOR = 2.51; 95%CI 1.34–4.71], and postoperative complications [AOR = 3.52; 95%CI 1.35–5.01].ConclusionThe average post-cesarean hospital stay is 2.71 days, with duration influenced by factors such as age, distance to the hospital, access to antenatal care, income, insurance, and the presence of complications. Targeted interventions, such as improving access to antenatal care, providing financial support, and proactively managing complications, can improve outcomes.